Physiological responses and variation in secondary metabolite content among Thai holy basil cultivars (Ocimum tenuiflorum L.) grown under controlled environmental conditions in a plant factory - Chutimanukul, Panita; Jindamol, Hathairut; Thongtip, Akira; Korinsak, Siripar; Romyanon, Kanokwan; Toojinda, Theerayut; Darwell, Clive Terence; Wanichananan, Praderm; Panya, Atikorn; Kaewsri, Wilailak; Auvuchanon, Anyamanee; Mosaleeyanon, Kriengkrai; et al. (Frontiers in Plant Science, 2022)
Holy basil (Ocimum Tenuiflorum L.) is a widely used herb containing several bioactive compounds of interest for the food and pharmaceutical industries. Plant factories using artificial lighting (PFAL) is a modern agricultural system that offers opportunity to improve crop production and stabilizes productivity in many herbal plants. However, little is known about the variation among holy basil varieties that can be cultivated and provide reasonable biomass and bioactive compounds in PFAL. We therefore evaluated 10 Thai accessions and two commercial cultivars in a PFAL (with hydroponic cultivation) to categorize cultivar characteristics by investigating physiological responses and secondary metabolite variation at plant flowering stage. Among Thai varieties, net photosynthetic rate (Pn) was significantly highest in varieties OC059 and OC081. The greatest growth and biomass measures were observed in OC064. Antioxidant capacity also varied, with the greatest accumulation of total phenolic compounds (TPC), flavonoids, and antioxidant activity by DPPH assay in OC064, and highest terpenoid content in OC194. The accumulation of major compounds confirmed by showing the highest levels of eugenol in OC057, OC063, OC194, and OC195 and methyl eugenol in OC072 and OC081. The highest α-humulene content was found in OC059. PCA based on physiological responses and secondary metabolites indicate that OC064 was clearly distinguished from other cultivars/accessions. These findings demonstrate variation across holy basil accessions for physiologic responses, antioxidant capacity, and secondary compounds in PFAL. These insights lead to identification of suitable varieties which is the most important step of developing an efficient method for producing high quality raw materials of Thai holy basil for supplying the foods and pharmaceutical industries.